Laparoscopic treatment of early-stage endometrial cancer with and without uterine manipulator: Our experience and review of literature. (June 2016) - Tinelli, Raffaele; Cicinelli, Ettore; Tinelli, Andrea; Bettocchi, Stefano; Angioni, Stefano; Litta, Pietro
Abstract: Objective: The aim of this study was to retrospectively compare in a series of 110 patients with early-stage endometrial cancer recurrence rate and surgical outcomes after total laparoscopic (LPS) hysterectomy with lymphadenectomy performed with or without uterine manipulator. Study design: 110 patients with clinical stage I endometrial cancer were enrolled in a retrospective study and underwent surgical staging comprised of LPS hysterectomy, bilateral salpingo-oophorectomy, and in all cases we performed systematic bilateral pelvic lymphadenectomy with uterine manipulator (Group 1, 55 patients) or without (Group 2, 55 patients). Results: The rate of positive cytology and LVSI did not significantly differ between Group 1 and Group 2. 1 patient of the Group 1 had a bladder injury and another patient of Group 2 had an ureteral stricture temporarily treated with a stent. 1 patient of the Group 1 had a bowel occlusion due to a port site hernia under the left 10 mm port, resolved with a bowel resection and an end-to-end anastomosis. In 1 patient of the Group 1 and 2 patients of Group 2 we observed a vaginal cuff dehiscence and in 1 case of Group 2 a pelvic lymphocyst was reported. Postoperative fever was reported in 3 patients of the Group 1 and in 5 patients of group 2 (p = 0.07). Conclusions: Our study confirms that use of uterine manipulator for laparoscopic treatment of endometrial cancer does not increase positive peritoneal citology, LVSI and recurrence rate. Highlights: 110 patients with stage I endometrial cancer underwent surgical staging with or without uterine manipulator. No significant difference in recurrence rate was observed between the two groups. use of uterine manipulator does not increase positive peritoneal citology and recurrence rate.